Efforts To Improve The Learning Of Inner Leg Passing With Conventional Methods In Class Vii Students At Integrated Muhammadiyah Smp In The City Of Bengkulu - Wahyuni, Armiyanti; Ferdiansyah, Rahmat; Martiani, Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the Efforts to Improve Learning of Inside Foot Passing with Conventional Methods for Grade VII Students at SMP Muhammadiyah Terpadu Kota Bengkulu. This type of research is classroom action research, the research conducted intends to find information about the implementation of the learning model delivered with classroom action treatment, namely the stages of the cycle in learning. The sample in this study was grade VII students at SMPN Muhammadiyah Terpadu Kota Bengkulu totaling 16 students. The results of the study showed that the action with the conventional passing method carried out in 2 cycles with each cycle 2 meetings was proven to be able to improve the skills of passing the inside of the foot in futsal games at SMP Muhammadiyah Terpadu Kota Bengkulu with initial data of 4 students completing the game with a percentage of 25% then learning was carried out with actions using conventional methods, an increase in students completing the game was obtained by 6 students with a percentage of 38% which shows that the achievement indicator has not been achieved so that further action is needed in cycle I, the second meeting, an increase in students completing the game was obtained by 11 students with a percentage of 69% which shows that the achievement indicator has not been achieved so that further action is needed in cycle II, the first meeting, an increase in students completing the game was obtained by 12 students with a percentage of 75% which shows that the achievement indicator has not been achieved so that further action is needed in cycle II, the second meeting, an increase in students completing the game was obtained by 14 students with a percentage of 94% which shows that the achievement indicator has been achieved so that the research is sufficient in cycle II, the second meeting.